The problem of fatigue in patients with systemic lupus erythematosus according to the data on a Russian RENAISSANCE cohort - E. A. Aseeva; S. K. Solovyev; N. Yu. Nikishina; G. M. Koilubaeva; T. A. Lisitsyna; E. L. Nasonov (Современная ревматология, 2020)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a wide range of clinical manifestations. Numerous observations and surveys of patients have shown that the most common symptom of SLE is fatigue complaints in 51 to 90% of patients.Objective: to determine the significance of fatigue in the general health status of RENAISSANCE cohort patients with SLE who were hospitalized in the Clinic, V.A. Nasonova Research Institute of Rheumatology.Patients and methods. The investigation included SLE patients aged 18 years and older who met the 2012 SLICC criteria. The standard examination accepted in the management of patients with SLE was made. Disease activity was determined by SLEDAI-2K; irreversible lesions in various organs were identified using the SLICC damage index. The SF-36 and the LupusQoL questionnaires were used to assess health-related quality of life (HRQOL) and the FACIT-Fatigue scale was applied to measure fatigue.Results and discussion. The investigation enrolled 328 patients, mainly women (91%); the mean age was 34.4±11.5 years; the duration of the disease was 106.3±97.9 months. In this group, moderate and high disease activities (SLEDAI-2K scores of 6–10 and 11–19, respectively) were observed at approximately the same frequency. At the time of inclusion, more than half (56.5%) of the patients already had various irreversible organ lesions. At Visit 1, the FACIT-Fatigue scale showed that fatigue was present in 148 (45%) of the 328 patients. According to the presence of fatigue, the patients were divided into two groups. Group 1 included 148 patients with fatigue; Group 2 consisted of 180 patients without fatigue. The Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) and anti-DNA antibody levels were significantly higher in the fatigue group (p=0.01 and p=0.02, respectively); the patients also had decreased HRQOL according to 7 LupusQol domains (p<0.001). The patients with fatigue were significantly more likely to receive intravenous glucocorticoids and rituximab. At 12 months after the start of treatment, the patients with fatigue were found to have a statistically significant reduction in disease activity, as well as normalization of anti-DNA antibody levels, improvements in HRQOL according to the LupusQol domains, and less severity of fatigue according to the FACIT-Fatigue scale.Conclusion. Fatigue was detected in almost half (45–53%) of SLE patients. It is associated with a higher disease activity by SLEDAI-2K and with a high anti-DNA antibody level. The patients with fatigue are observed to have an obvious worsening of HRQOL according to all LupusQol domains.